2010
DOI: 10.1242/dmm.002642
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of Menkes disease reveals a role for DmATP7 in copper absorption and neurodevelopment

Abstract: SUMMARY Human Menkes disease is a lethal neurodegenerative disorder of copper metabolism that is caused by mutations in the ATP7A copper-transporting gene. In the present study, we attempted to construct a Drosophila model of Menkes disease by RNA interference (RNAi)-induced silencing of DmATP7, the Drosophila orthologue of mammalian ATP7A, in the digestive tract. Here, we show that a lowered level of DmATP7 mRNA in the digestive tract results in a reduced copper content in the head and the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Given that CUA-1.1 abundance was not altered under the dpy-7 promoter, and that cua-1 transcript levels increased under copper-limiting conditions, hypodermal cua-1 may respond to copper deficiency transcriptionally. MTF-1 is known to transcriptionally induce both ATP7 and metallothionein expression in Drosophila, but no MTF-1 homolog has been defined in C. elegans (45)(46)(47)(48). MTF-1-independent metal-responsive transcription factors have been identified, suggesting the existence of other copper-responsive transcription factors that could regulate cua-1 expression in the hypodermis (43,49).…”
Section: Discussionmentioning
confidence: 99%
“…Given that CUA-1.1 abundance was not altered under the dpy-7 promoter, and that cua-1 transcript levels increased under copper-limiting conditions, hypodermal cua-1 may respond to copper deficiency transcriptionally. MTF-1 is known to transcriptionally induce both ATP7 and metallothionein expression in Drosophila, but no MTF-1 homolog has been defined in C. elegans (45)(46)(47)(48). MTF-1-independent metal-responsive transcription factors have been identified, suggesting the existence of other copper-responsive transcription factors that could regulate cua-1 expression in the hypodermis (43,49).…”
Section: Discussionmentioning
confidence: 99%
“…Several observations support this view. First, on the understanding that D. melanogaster and mammalian has conserved molecular mechanisms for metal uptake and efflux, distribution and regulation systems Bahadorani et al 2010;Hua et al 2010;Southon et al 2010;Tiklová et al 2010;Kaler 2011), it is not surprising that acute or chronic excess Fe, Mn and Cu exposure negatively affect life span and locomotor functionality in D. melanogaster. Moreover, we found that the reduction in life span and mobility abilities were related to abnormal accumulation of these metals in the fly's head.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila melanogaster has become an attractive organism to model PD (for a review, see Pienaar et al 2010). Since the fly expresses many proteins involved in the metabolism of those biometals such as ferritin (Missirlis et al 2006), transferrin (Yoshiga et al 1999), iron regulatory proteins (Muckenthaler et al 1998), Malvolio (Southon et al 2008), divalent metal transporter (DMT1; Au et al 2008) and DmATP7 Bahadorani et al 2010) similar to human, the aims of the present study were (i) to assess the effect of acute (up to 5 days) and chronic (up to 15 days) exposure to iron, manganese and copper on the survival and locomotor function (i.e. climbing capability) of Canton-S D. melanogaster, (ii) to investigate whether metals accumulate in the fly's brain, (iii) to determine brain dopaminergic neuronal damage by the metals in female F1 (TH-GAL4/UAS-GFP) Drosophila flies.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional levels of ETHRA and ETHRB were normalized to those of the housekeeping gene b-actin gene Act57B, as done previously by Bahadorani et al (2010), in both experimental and controls (genotype: w 1118 ; +; +). The expression levels of ETHRA and ETHRB in experimental animals were then calculated as percentage changes relative to those in controls using the 2 2DDC T method (Livak and Schmittgen 2001).…”
Section: Molecular Biologymentioning
confidence: 99%